UPAYA PEMERINTAH MENINGKATKAN IKLIM INVESTASI - Made Warka (Perspektif, 2006)
Government in performing national development really needs capital investment whether capital investment inside the country or capital investment in outside the country, especially in industrial sector. Difficulties in performing the development are caused by lack of capital, ability in technology, knowledge, experiences and skills, and it ’s nature is multi-dimensionality, therefore there is a need of a big capital. The efforts of central government and City government in attracting investment have been performed such as the lessen of bureaucracy paths, the given of guarantee to political and security stability, and law certainty besides the giving of incentive forms to the investors, therefore, they will be believe and have faith that capital investment in industrial sector will give much advantages to investors.